2018
DOI: 10.7196/samj.2018.v108i10.13148
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anaemia and clinical outcomes in the South African Surgical Outcomes Study

Abstract: In high-income countries, preoperative anaemia has been associated with increased postoperative morbidity and mortality. [1] Preoperative anaemia is a common problem, with three large database studies in Europe and America estimating the prevalence to be between 25% and 30%. [2-4] Anaemia is also associated with increased perioperative blood transfusions, a practice independently associated with morbidity and mortality. [5] Growing evidence supports increasingly restrictive transfusion strategies in surgical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 5 publications
(10 reference statements)
3
21
0
Order By: Relevance
“…In South Africa, perioperative anaemia is associated with a greater need for critical care services and increased complications. 6 Jadhunandan et al found a high prevalence of perioperative anaemia in this group of high-risk general surgical patients. Importantly, moderate to severe perioperative anaemia is associated with an increased postoperative mortality.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…In South Africa, perioperative anaemia is associated with a greater need for critical care services and increased complications. 6 Jadhunandan et al found a high prevalence of perioperative anaemia in this group of high-risk general surgical patients. Importantly, moderate to severe perioperative anaemia is associated with an increased postoperative mortality.…”
mentioning
confidence: 75%
“…The prevalence was higher than that found in the South African Surgical Outcomes Study (SASOS). 6 There are several reasons for this observation, although they are mostly related to the study population of Jadhunandan et al, 2 which included more patients with cancer and chronic medical conditions which adversely affect red blood cell production. 2,6 Improving oxygen delivery is a proposed mechanism for potentially reducing postoperative morbidity and mortality.…”
mentioning
confidence: 99%
“…Since then, perioperative research has been conducted in SA to quantify the LCoGS indicators and identify health system gaps in workforce, [13,14] infrastructure [15][16][17] and quality. [18][19][20] While more than 96% of South Africans live within 2 hours of a government hospital, [21] quality surgical care is variable and lags behind global standards. [20] Governance, financing, service delivery, infrastructure, the workforce and data systems must be optimised to improve surgical outcomes at a national level.…”
Section: Editorialmentioning
confidence: 99%
“…8 The association between PA and a higher risk of postoperative critical care admission was confirmed by Marsicano and colleagues in a sub-analysis of data from the South African Surgical Outcomes Study (SASOS). 9 The authors found that SASOS patients with PA were at a 49% higher risk of requiring critical care services postoperatively when compared with non-anaemic patients. 9 Patients with PA also have a higher risk of postoperative mortality (PM) when compared with nonanaemic patients.…”
Section: Introductionmentioning
confidence: 96%
“…4 Most of these prevalence estimates, ranging between 28.7% and 47.8%, are based on observations in mixed surgical populations. [7][8][9][10] Another important finding from studies investigating PA in mixed surgical populations is the association of this condition with an increased risk of postoperative complications. [7][8][9][10] A study by Musallam et al of 227 425 non-cardiac surgery patients (of which 30.4% had PA)…”
Section: Introductionmentioning
confidence: 99%